Synthesis and characterization of nickel doped ternary oxide thin film as electrode materials for supercapacitor application - Cissan Sylvanus; Jemima Ogwo; Sylvanus Isaac (Engineering and Technology Journal)
The over-dependence on fossil fuels for energy generation, especially in developing countries like Nigeria, is a major setback to the economy. There is a hike in its price, hence the need to commercialize a renewable form of energy such as solar energy. Solar energy's intermittent nature is a barrier, requiring an efficient, affordable, clean energy storage mechanism such as a supercapacitor. Electrodes are a supercapacitor's basic components, and optimizing an electrode material leads to wide electrochemical applications. In this study, Ni-doped  thin films were synthesized by electrochemical deposition, and the optical, morphological, and electrochemical properties were investigated through different characterization techniques. The optical properties were analyzed using a UV-Vis spectrophotometer, a decrease in absorbance (25%), absorption coefficient , extinction coefficient , real dielectric constant and energy band gap (1.8 eV) of the film with the highest concentration of Ni was observed. The SEM result shows the films densely adhered to the substrate but unevenly distributed with imperfections (cracks and voids) as the concentration of Ni increases. The specific capacitance of the film  was measured to be 410.8 F/g, 235.7 F/g, and 184.2 F/g in the presence of 6M KOH electrolyte at a scan rate of 10 mV/s, 20 mV/s, 50 mV/s, respectively at the same current density of 0.3 A/g with the highest electrical conductivity of .These results indicate the promising features of Ni-doped  thin films are used as electrode material for supercapacitor applications.